O-4 A co-speciality cross-boundary model of supportive care: an innovative approach to caring for the palliative care needs of heart failure patients. (20th March 2022) - Atkinson, Clea; Hughes, Sian; Richards, Len; Sim, Victor; Phillips, Julie; John, Imogen; Yousef, Zaheer
Abstract : Background: Heart failure (HF) is an increasingly prevalent condition associated with poor quality-of-life and high symptom burden. Patients experience an unpredictable disease trajectory and repeated acute admissions towards the latter stages of life. As patients reach ceilings of survival-extending interventions, their priorities may be more readily addressed through the support of palliative care services, however the best model of care remains unestablished. Objectives: We aimed to create and evaluate a co-specialty cross-boundary service model for HF patients that better provides for their palliative care needs in the latter stages of life, whilst delivering a more cost-effective patient journey. Methods: In 2016 the Heart Failure Supportive Care Service (HFSCS) was established to provide patient-centered holistic support to advanced HF patients. Patient experience was evaluated through questionnaires that were developed and distributed in mid-2018 and end-of-2020. Actual and indexed hospital admission data (in-patient bed days pre-/post-referral) were used allowing statistical comparisons by paired student t-tests. Cost mapping analysis allowed approximation of cost-saving benefits. Results: From 2016–2020, 236 patients were referred to the HFSCS. Overall, 75/118 questionnaires were returned. Patients felt the HFSCS delivered compassionate and coordinated care (84% and 80%) that improved symptoms and quality of life (80% and 65%). Introduction of the HFSCS resulted in a statistically significant reduction in HF-related admissions: actual days 18.3 to 4 days (p<0.001), indexed days 0.05 to 0.032 days (p=0.03), and a 50% reduction in hospital deaths over 5 years. Cost mapping revealed an estimated average saving of at least £10, 218.36 per referral and a total estimated cost saving of approximately £2.4 million over 5 years. Conclusion: This service design demonstrates that a co-specialty cross-boundary method of care delivery can successfully provide the benefits of palliative care to HF patients in a value-based manner, whilst meeting the priorities of care that matter to patients most.